New document on Jerónimo de Pasamonte and the Monasterio de Piedra (Castilla. Estudios de Literatura, 2022)
The discovery of a new document linking Jerónimo de Pasamonte with the Monasterio de Piedra is reported. This document is related to those that were already known, and it is briefly explained that it was in the Monasterio de Piedra where Jerónimo de Pasamonte was able to compose the apocryphal Quixote.
Keywords: Jerónimo de Pasamonte; Monasterio de Piedra; apocryphal Quixote of Avellaneda; Cervantes and Pasamonte; Cervantes and Avellaneda